AB0976 Do Ultrasound Color Histograms Show Better Musculoskeletal Changes?. (10th June 2014) - Mendonça, J.A.; Vierhout, C.V.; Schincariol, N.; Peron, F.; Pedri, L.; Provenza, J.R.
Abstract : Background: Ultrasonography with high frequency linear array probe, besides allowing a better resolution in the GS scale (grey scale), is able to identify color images standards. This is the case of the RGB color images, which are formed through the information of additive primary colors, such as R - Red, G – Green and B - Blue, orange, indigo, magenta, blue and yellow, generating a histogram. The objective of color models is to allow color specification in a universally accepted standard format 1 . Objectives: To detect synovitis (SYN) and calcifications (calcifs), through histograms, i.e., color image standards and to correlate the area measurement with the GS. Methods: Ten patients have been assessed, 2 males and 8 females with average age 40.7 years; a total of 104 SYN and calcifs measurements in cm 2 were performed in the dorsal radiocarpal joint (dRC); triangular fibrocartilage complex (TFCC); dorsal metacarpal phalanx (MCP) and lateral and medial knee suprapatellar recesses. Four patients exhibited chondrocalcinosis, 5 patients osteoarthritis and one patient psoriatic arthritis. For each GS measurement, one measurement was performed for each color image standard, at different times and at random, in order not to see or remember prior measurement data. For the Spearman correlation analysis, the program IBM SPSS Statistics 19 was used. Results: Average ± SD of the image standards: RGB SYN 16.96±0.25 cm 2 ; Indigo SYN 6.43±0.07 cm 2, RGB calcif 0.03±0.00 cm 2 ; Indigo calcif 0.06±0.03 cm 2 ; GS SYN 16.13±0.35 cm 2 and GS calcif 0.56±0.01 cm 2 . Correlation of the color images standards: RGB dRC SYN and Indigo dRC SYN: r=1.0; p<0, 001 . Indigo dRC SYN and RGB suprapatellar SYN: r=1, 0; p<0, 001 . RGB MCP SYN and Indigo MCP SYN: r=1, 0; p<0, 001 . Indigo dRC calcif and RGB TFCC calcif: r=1.0; p<0, 001 . The RGB and Indigo measurement standards when correlated with GS for SYN and calcifs were not statistically significant (p=0.333 to 0.667). Conclusions: The color images standards of the mode-B function, represented by the histogram, assesses SYN and calcifs through the tones RGB, orange, indigo, magenta, blue and yellow. The standards RGB and Indigo seem to better set out these ecotextural damages, detected through the area measurements in cm 2 . However, future studies are required to further ground these ultrasonographic findings. References: Marques Filho, O; Vieira Neto, H. Processamento Digital de Imagens, Rio de Janeiro: Brasport, 1999. ISBN 8574520098. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.2977